Direct Ras Inhibitors Identified from a Structurally Rigidified Bicyclic Peptide Library - Upadhyaya, Punit (2014)
A one-bead-two-compound (OBTC) library of structurally rigidified bicyclic peptides was chemically synthesized on TentaGel microbeads (90 μm), with each bead displaying a unique bicyclic peptide on its surface and a linear encoding peptide of the same sequence in its interior. Screening of the library against oncogenic K-Ras G12V mutant identified two classes of Ras ligands. The class I ligands apparently bind to the effector-binding site and inhibit the Ras-Raf interaction, whereas the class II ligand appears to bind to a yet unidentified site different from the effector-binding site. These Ras ligands provide useful research tools and may be further developed into therapeutic agents.